Welcoming the Newlyweds:: Charivari, Shivaree, Serenade, Banjo, and Saluting in Nova Scotia, 1917-c.1975 - Greenhill, Pauline (Acadiensis, 2009)
Abstract In rural Nova Scotia, until the 1970s, charivaris followed certain marriages and occasionally other notable socio-cultural events (either contentious or praiseworthy). This tradition’s complex meaning helps to explain its persistence as part of the ongoing scrutiny and sanctioning of behaviour in rural communities. Its stated purpose as a "welcome," noise-invoking names, cacophonous ritual means, accompanying sexualized trickery, and rural location demonstrate that the event’s main concerns were with the reproduction of individuals and communities while placing the responsibility for this mainly upon women.